Indigenous knowledge and Chemistry teaching: Experimental scripts based on salt extraction from water hyacinth (Research, Society and Development, 2025)
Law No. 11.645/2008 establishes the mandatory teaching of Indigenous history and culture in Brazilian basic education; however, the inclusion of Indigenous knowledge in Chemistry teaching remains punctual and generally disconnected from systematized experimental practices. The objective of this article is to develop and systematize experimental scripts based on the traditional technique of extracting salt from water hyacinth practiced by the Waurá people, articulating concepts of Analytical Chemistry with an intercultural perspective aimed at initial teacher education. This study consists of qualitative research focused on the development of didactic material, grounded in bibliographic research and experimentation conducted in a university laboratory. Based on documentary descriptions of the Indigenous practice, three experimental scripts were elaborated, addressing stages of collection, drying, combustion, solubilization, and analysis of the obtained salt, mobilizing concepts such as mass conservation, solubility, precipitation titration, and gravimetry. The results indicate that the water hyacinth salt technique can be translated into experimental activities consistent with the contents of Analytical Chemistry without disregarding its cultural and historical dimensions. It is concluded that the proposed scripts constitute a methodological pathway for integrating documented Indigenous knowledge into university-level Chemistry teaching, contributing to a more critical, contextualized, and epistemically sensitive teacher education.